The Role of Cycling in Sustainable Urban Life: Perception of Cyclists in Turkey - Ceyiz, Senem (Canadian Center of Science and Education, 2019)
The aim of this study was to determine the perceptions of bicyclists to promote the use of bicycles in the cities. The sample was selected using simple random sampling method. A total of 1087 bicyclists, including 178 women and 909 men, who used bicycles in their everyday lives in the city, voluntarily participated in the research. The study was a descriptive research in the survey model and quantitative research approach was adopted in the research. Data were collected with “Bike Use Dissemination Scale” developed by Çeyiz (2019). The scale consists of two parts; a personal information form and expressions of participants’ dissemination of bicycle use. The t-test was used for the variables consisting of the bipartite groups and the One-Way ANOVA was used for the variables consisting of more than two groups. According to the data obtained from the bicyclists participating in the survey, there was a significant difference in the dimensions of security and dissemination by gender. It was found that women bicyclists’ safety perceptions were more negative than men’s perception; and their perceptions of the spreading dimension were more positive than the male bicyclists.
Keywords: 11. Sustainability; 16. Peace & justice; 12. Responsible consumption